2014
DOI: 10.4314/jab.v76i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Étude de la croissance du bananier plantain (<i>Musa sp</i>., AAB, cultivar Corne 1) dans les régions de Yamoussoukro et Azaguié (Cote d’Ivoire)

Abstract: Conclusion et application de la recherche : Les différentes variations observées des paramètres étudiés signifient que ceux-ci sont en modification perpétuelle durant la croissance du bananier plantain. C'est donc à ce titre que la modélisation de la croissance du bananier plantain, en utilisant les données expérimentales, peut être proposée comme une voie de solution pour la maitrise de la variabilité des paramètres dans les zones de production et pour deux types de traitement. Mots clés : Bananier plantain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
1
6
1
1
Order By: Relevance
“…These pH values were relatively higher than the pH values (4.7-5) obtained by Kabrah et al (2000) for the soils under palm groves in the Mé region (Côte d'Ivoire). Moreover, the pH values of the present study are very close to those for Kouamé (2014) where the pH values were between 5.22 and 5.39 for the soils of Yamoussoukro, and between 5.90 and 6.00 for the soil of Azaguié . The results of these authors also confirm the near constancy of the pH up to 30 cm depth.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These pH values were relatively higher than the pH values (4.7-5) obtained by Kabrah et al (2000) for the soils under palm groves in the Mé region (Côte d'Ivoire). Moreover, the pH values of the present study are very close to those for Kouamé (2014) where the pH values were between 5.22 and 5.39 for the soils of Yamoussoukro, and between 5.90 and 6.00 for the soil of Azaguié . The results of these authors also confirm the near constancy of the pH up to 30 cm depth.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the mangosteen, rubber and fallow plots had soils with low total phosphorus content according to the classification scale of the "Comité d'Etude et de Development de la Fertilisation" (COMIFER) (Vedie, 2008). These total phosphorus contents were lower than those obtained by Kouamé (2014), who found total phosphorus concentrations of 229.08 mg/kg and 214.75 mg/kg respectively for the 0-20 cm and 20-40 cm strata of the Azaguié soil. This difference could be due to plant cover and agronomic exploitation.…”
Section: Discussioncontrasting
confidence: 76%
“…In general, T1 treatment without fertilizer induced significantly (p ≤ 0.05) lower values of growth, development and yield parameters compared to treatments with fertilizer (T2-T6). This lack of improvement in performance indicates the positive effect of fertilizer on plantain growth as highlighted by [21]. When banana was subjected to fertilizers, data showed that PITA 3 performed in growth by an increase of height and circumference with T6 treatment, unlike T5 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the corms of the subjects placed on the amended substrates was influenced by the administration of composts rich in mineral matter, in particular in Nitrogen, Phosphorus and Potassium, which are activating elements for the growth and development of the plant (Kouamé et al, 2014).…”
Section: Discussionmentioning
confidence: 99%